27-x/3=13

Simple and best practice solution for 27-x/3=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27-x/3=13 equation:



27-x/3=13
We move all terms to the left:
27-x/3-(13)=0
We add all the numbers together, and all the variables
-x/3+14=0
We multiply all the terms by the denominator
-x+14*3=0
We add all the numbers together, and all the variables
-1x+42=0
We move all terms containing x to the left, all other terms to the right
-x=-42
x=-42/-1
x=+42

See similar equations:

| -3n-2=6 | | 1+x/7=4 | | 1/12(x-32)=1+x | | 18=5x+855 | | 4y+7-7=2(y+3) | | 25y+2=52 | | 30=w/4+15 | | 1/12(-32)=1+x | | 9c+6=60 | | 14+12x+14x-2=180 | | X^2+15x-24=0 | | 2v+8-10=2+4v | | 8r-4=16 | | 5x+18=855 | | -8(5-7c)=184 | | 5-2g=1/2g-4 | | 1/11(-32)=1+x | | 1.5(x)=90-x | | X+x*2-4+x*3+3+(x*2-4)*2-5=785 | | 3x+4x=10x | | 855=3x+18 | | 5y+⅖=10.4 | | 6x2–x–2=0 | | 4u=-2(-u-5) | | 6x-4/2-9x+3/4=1 | | 967=d−–406 | | 3+2x=2(-x+3)-11 | | 7x-3+10-2x=62 | | 2(9t+10)=56 | | 7+p=241 | | 90=81-2x-51 | | y=-81(91)+33+ |

Equations solver categories